Impact of climate change shocks on economic growth: A new insight from non-linear analysis - Khurshid, Nabila; Fiaz, Asma; Khurshid, Jamila; Ali, Kashif (Frontiers in Environmental Science, 2022)
Despite the fact that Pakistan's contribution to GHG emissions is low (0.8%) when compared to other countries but it is one of the hardest hit by climate change. The present study is an attempt to identify the impact of climate change on economic growth. The non-linear autoregressive distributional lag (NARDL) technique is used to estimate the asymmetric effect of climate change on the economic growth of Pakistan. Annual data covering the years 1980 to 2021 are used for empirical analysis. It is noteworthy to reiterate that CO2 emissions and mean temperature pose asymmetrical results concerning economic growth, both in the long-run and short-run. CO2_POS and CO2_NEG have a negative impact on economic growth, whereas MEANT_POS has a positive impact on economic growth and MEANT_NEG has a negative impact. Precipitation has a positive and significant long-term influence on economic growth. Research findings indicate that comprehensive mitigation policies at the nationwide and worldwide levels are required to limit human-caused climate change in Pakistan. At national level, tree planting projects and safeguard greenery at all costs while at international level, policies needed for adoption of mitigation strategies to control climate change.